BEHAVIOR OF URANIUM DURING CRYSTALLIZATION OF AN ALKALIC MELT - Kozlova P.S.; Gurvich M.Y.; Muravitskaya G.N. (My University, 1988)
The article considers a 1- to 3-mm thick tongue that is emplaced in skarn-altered limestone, branches off an alkalic syenite dike and has a rapidly tapering lateral offshoot. We proved by f-radiography that the uranium distribution within this alkalic syenite tongue is extremely uneven. Its central part is virturally devoid of uranium. At the inner contact, this element has accumulated in small, unevenly scattered grains of accessory minerals, chiefly zoned cyrtolite, ferrithorite and orthite. Such distribution indicates that there was considerable movement of uranium in the crystallizing melt together with the fluid phase.